An Experimental Analysis on Texture Based classification Using Learning Algorithms - Bhaskari, D. Lalitha; Sathish, Ch. Pavan (International Journal of Computer Sciences and Engineering, 2025)
In this digital era, with the advancements of technology a major role is being played by Information and Communication Technology in agriculture. Especially the issues related to agriculture such as real-time crop detection and monitoring, leaf identification is still a challenging task for the researchers and practitioners. Automatic detection of the crop type and its growth by analysing the colour and size of the leaves helps the farmers to take immediate advice from the botanical domain expert. The work in this paper deals with study and implementation of texture based classification and annotation of groundnut crop leaves using machine learning algorithms like HAAR, HOG and LBP. A set of trained and untrained images are employed in this task. Experiments are conducted using the cascade trainer tool in MATLAB 2016 by varying several parameters and selecting regions-of-interest on the crop for training. Later, the impact of each of the parameters on the above algorithms are recorded and well described in this paper. Furthermore, from the perspective of number of objects detected, it is noticed that LBP has yielded better results than HAAR and HOG.